Activities of the summer party of the 31st Japanese Antarctic Research Expedition in 1989–1990 - Masashi Sano (National Institute of Polar Research, 1996)
The 31st Antarctic Research Expedition (JARE) consisted of 55 members, of which the 30 members of the wintering party at Syowa Station were led by Y. NAITO, 8 members of the wintering party at Asuka Station by K. SHIRAISHI and 17 members of the summer party by M. SANO. In addition, two Chinese scientists and two Belgian scientists participated. The icebreaker SHIRASE, leaving Tokyo on 14 November 1989,after calling at Fremantle, Western Australia, arrived at Breid Bay on 17 December. The helicopter and surface transportation of 173t of cago including two AS-350 helicopters, 8 wintering members and 14 members of the summer SΦr Rondane Mountains expedition from the ship to Asuka Station were completed by 30 December. The ship reached Syowa Station on 14 January 1990,it needed 15 days to approach Syowa Station because the pack ice and first ice in Lutzow-Holm Bay were very thick and heavy compared with a normal year. Unloading of 624t of the cargo, and the summer operations including field research work, relief of the observation team, and construction and renewal of some facilities were completedby 31 January 1990. The SHIRASE left Syowa Station 1 February and arrived again at Breid Bay on 7 February, and picked up the field party and two AS-350 helicopters. On the way from Breid Bay to Sydney, Australia, the ship stopped over at Amundsen Bay for field work between 12-19 February 1990. The SHIRASE arrived at Sydney on 20 March 1990. Members of the summer party of JARE-31 and the wintering party of JARE-30 returned to Narita by air on 28 March 1990. The SHIRASE arrived at Tokyo on 13 April 1990. The following scientific activities were carried out during the summer operations of JARE-31 : a) geological, biological and geodetic observations by helicopter in the SΦr Rondane Mountains region; b) biological and oceanographic observations in the Syowa Station area; c) an oversnow traverse for unmanned meteorology and upper atmosphere physics observations to Mizuho Station from Syowa Station; d) geological, biological, ...